2017
DOI: 10.2298/jsc161016036b
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial, antioxidant, cytotoxic and anticholinesterase activities of water-soluble polysaccharides extracted from microalgae Isochrysis galbana and Nannochloropsis oculata

Abstract: The present work is carried out to evaluate potential applications of aqueous extracts of two microalgae Isochrysis galbana (PEA) and Nannochloropsis oculata (PEB) containing mainly polysaccharides. The monosaccharide composition of microalgal extracts was determined. GC-MS analyses after derivatization show that glucose is the major compound in both microalgae PEA (56.88 %) and PEB (68.23 %). Mannitol (38.8 %) and inositol (20.32 %) are respectively the second major compounds in PEA and PEB. Silylation of mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…In 2017, Hafsa and colleagues reported the extraction of some hydrophilic polysaccharides from microalgae such as Isochrysis galbana and Nannochloropsis oculate, which possessed antimicrobial, anticancer, and anticholinesterase properties [169]. In 2018, Mebrek and colleagues reported that barley-derived beta-glucan, a homopolysaccharide, has moderate antioxidant and enzyme inhibitory activities.…”
Section: Anticholinesterase Activity Of Polysaccharidesmentioning
confidence: 99%
“…In 2017, Hafsa and colleagues reported the extraction of some hydrophilic polysaccharides from microalgae such as Isochrysis galbana and Nannochloropsis oculate, which possessed antimicrobial, anticancer, and anticholinesterase properties [169]. In 2018, Mebrek and colleagues reported that barley-derived beta-glucan, a homopolysaccharide, has moderate antioxidant and enzyme inhibitory activities.…”
Section: Anticholinesterase Activity Of Polysaccharidesmentioning
confidence: 99%
“…exhibited significant antioxidant activity revealed through antioxidant assays (Tannin-Spitz et al, 2005;Sun et al, 2014;Amna Kashif et al, 2018). In addition, polysaccharide extract of I. galbana and N. oculata has the antioxidant capacity and antiproliferative activity against HeLa cells (Hafsa et al, 2017). Nostoglycan, a polysaccharide isolated from Nostoc sphaeroides has been reported to give protection from oxidative stress, and also to stop the growth of lung cancer cells as well as to promote apoptosis through activation of the caspase-3 pathway (Li et al, 2018).…”
Section: Polysaccharidesmentioning
confidence: 99%
“…and Scenedesmus sp . – DPPH radical and hydroxyl radicals [ 86 ], Chlamydomonas reinhardtii [ 87 ] and Rhodella reticulata – superoxide radical ion [ 88 ]; as well as polysaccharides from Isochrysis galbana – superoxide radical ion and hydroxyl radical, H 2 O 2 [ 89 ], Nannochloropsis oculata – DPPH radical [ 90 ] and sulphated polysaccharide from Navicula sp . – DPPH radical, ABTS radical [ 91 ].…”
Section: Antioxidant Featurementioning
confidence: 99%